1988
DOI: 10.1039/p19880001251
|View full text |Cite
|
Sign up to set email alerts
|

Terpenylations using (R)-(–)-α-phellandrene. Synthesis of the (3S,4R)-8,9-dihydro-o- and -p-cannabidiols, their iso-THC's, and the natural dihydrochalcone (3S,4R)-(+)-linderatin

Abstract: ChemInform Abstract Catalyzed by TosOH, (R)-(-)-α-phellandrene (I) reacts with olivetol (II) to give the dihydro-p-and -o-cannabidiols (III) and (IV). At 80 rc C under the acid conditions the latter retrogresses to the former and both cyclize to give the p-isotetrahydrocannabinol (V) with 51% yield and only 3% of the corresponding o-isomer. Terpenylation of the dihydrochalcone (VI) yields the natural meroterpene linderatin (VII).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1988
1988
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 2 publications
2
21
0
Order By: Relevance
“…The previously known substances 2 ,4 ,6 -trihydroxydihydrochalcone (2) (Crombie et al 1988;Hufford and Lasswell 1978), 2 ,6 ,4-trihydroxy-4 -methoxydihydrochalcone (3) (Hermoso et al 2003;Mabry et al 1975), 2 ,6 -dihydroxy-4 -methoxydihydrochalcone (4) (Hermoso et al 2003;Nilsson 1961), 5,7-dihydroxyflavanone [(2S)-pinocembrin] (5) (Bick et al 1972;Miyakado et al 1976), 2 ,6 -dihydroxy-4 ,4-dimethoxy dihydrochalcone (6) (Nilsson 1961) and (2R,3R)-3,5,7-trihydroxy-3-O-acetylflavanone (7) (Kumazawa et al 2002;Tomás-Barberán et al 1993), were identified by their physical (mp, [˛] D ) and spectroscopic ( 1 H and 13 C NMR and mass spectra) data, including NMR 2D-COSY, HSQC and HMBC experiments that allowed the unequivocal assignment of their structures.…”
Section: Identification Of Compounds 2-7mentioning
confidence: 99%
“…The previously known substances 2 ,4 ,6 -trihydroxydihydrochalcone (2) (Crombie et al 1988;Hufford and Lasswell 1978), 2 ,6 ,4-trihydroxy-4 -methoxydihydrochalcone (3) (Hermoso et al 2003;Mabry et al 1975), 2 ,6 -dihydroxy-4 -methoxydihydrochalcone (4) (Hermoso et al 2003;Nilsson 1961), 5,7-dihydroxyflavanone [(2S)-pinocembrin] (5) (Bick et al 1972;Miyakado et al 1976), 2 ,6 -dihydroxy-4 ,4-dimethoxy dihydrochalcone (6) (Nilsson 1961) and (2R,3R)-3,5,7-trihydroxy-3-O-acetylflavanone (7) (Kumazawa et al 2002;Tomás-Barberán et al 1993), were identified by their physical (mp, [˛] D ) and spectroscopic ( 1 H and 13 C NMR and mass spectra) data, including NMR 2D-COSY, HSQC and HMBC experiments that allowed the unequivocal assignment of their structures.…”
Section: Identification Of Compounds 2-7mentioning
confidence: 99%
“…A simple, one-step synthetic approach to H2CBD could be based on the work of Crombie and co-workers 36 . Optimization of this reaction led to the isolation of H2CBD in a 71% yield (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another advantage of H2CBD (and other synthetic (−)‐CBD analogs in general) would be that it is purely synthetic compound and, thus, free from problems in the uncontrolled Cannabis cultivation and compound extraction (e.g., heavy water usage and use of pesticides/herbicides) . H2CBD was initially synthesized by the terpenylation of olivetol ( 18 ) with the allyl cation derived by p ‐TsOH treatment of α‐phellandrene ( 110 ), and the reaction conditions were optimized further to generate (±)‐H2CBD ((±)‐ 96 ) in higher yield (71 %) (Scheme ) . Their reaction strategy made the gram‐scale synthesis feasible, and it was also anticipated that the single‐step synthesis from food‐grade α‐phellandrene and olivetol would bring practicality to the chemical synthesis.…”
Section: Limonene Analogsmentioning
confidence: 99%
“…Ferruginene C shows the cytotoxicity in the HL‐60 cancer cell‐line (IC50: 13.7 μ m ) and binds weakly to the CB 2 and TPRV1 receptors, while no biological data of linderatin has been reported. There is the sole example of the synthesis of linderatin, and there have been no report on the synthesis of ferruginene C.…”
Section: Other Analogsmentioning
confidence: 99%